C‐band backscatter from a complexly‐layered snow cover on first‐year sea ice. Issue 16 (25th June 2014) - Fuller, M. Christopher; Geldsetzer, Torsten; Gill, Jagvijay P. S.; Yackel, John J.; Derksen, Chris; Pelto, Mauri; Kelly, Richard
Abstract We present a case study of observed and modelled C‐band microwave backscatter signatures for a complexly‐layered snow cover on smooth, land‐fast, first‐year sea ice. We investigate how complexly‐layered snow affects the backscatter, by comparing signatures with those for a simple snow cover, and through model sensitivity analysis. Backscatter signatures are obtained using a surface‐based scatterometer, on sea ice in Hudson Bay, Canada. Coincident in situ snow and ice geophysical measurements, and on‐ice meteorological observations, describe the snow cover formation and structure. A multilayer snow and ice backscatter model is used to iteratively add and subtract components of the complex snow cover to assess their impacts on the overall backscatter. For incidence angles between 20° and 70°, the backscatter from a complex snow cover on smooth first‐year sea ice is significantly higher than backscatter from a simple snow cover on similar sea ice. Sensitivity analysis suggests that rough ice layers formed within the complex snow cover and those superimposed at the sea ice interface are the physical mechanisms that affect an increase in surface and volume backscattering. This has implications for sea ice mapping, geophysical inversion and snow thickness studies. Copyright © 2014 John Wiley & Sons, Ltd.